Ab-initio investigation of preferential triangular self-formation of oxide heterostructures of monolayer $$\hbox {WSe}_{2}$$ WSe 2 - Soumya Ranjan Das (Nature Portfolio, 2020)
Abstract Triangular growth patterns of pristine two-dimensional (2D) transition metal dichalcogenides (TMDs) are ubiquitous in experiments. Here, we use first-principles calculations to investigate the growth of triangular shaped oxide islands upon layer-by-layer controlled oxidation in monolayer and few-layer $$\hbox {WSe}_{2}$$ WSe 2 systems. Pristine 2D TMDs with a trigonal prismatic geometry prefer the triangular growth morphology due to structural stability arising from the edge chalcogen atoms along its three sides. Our ab-initio energetics and thermodynamic study show that, since the Se atoms are more susceptible to oxygen replacement, the preferential oxidation happens along the Se zigzag lines, producing triangular islands of transition metal oxides. The thermodynamic stability arising from the preferential triangular self-formation of TMD based oxide heterostructures and their electronic properties opens a new avenue for their exploration in advanced electronic and optoelectronic devices.